CUSTOMER SATISFACTION TO QUALITY SERVICES IN LKMS BMT DARUSSALAM CIAMIS 2019 - Diyah Wikan Rachmatika; Risky Maidan Ilmy (Syari'ah Economics, 2020)
Service factor is one of the spearheads of companies in selling their products or services. The number of customers is very big influence from how to serve the customer. Even if the company has made a massive promotion or has improved the quality of the product or service offered, but without the support of good service, it will not get the desired results and the right target. The existence of complaints from some customers who mention the lack of friendliness of employees in the system services performed and the absence of a clear division of tasks between customer service and teller when doing service became the main reason in this study was conducted in BMT Darussalam Ciamis. The research method used is descriptive method and verification method with explanatory survey approach. Data collection technique used is non-probability sampling and the technique chosen is purposive sampling. Instrument data collection used in the form of questionnaire (questionnaire) and using likert scale. Data analysis techniques using simple linear regression analysis techniques and using analysis tools in the form of software SPSS (Statistic Product and Service Solution) version 19.0. for windows. The results of 96 respondents showed the quality of service influence on customer satisfaction BMT Darussalam Ciamis. Judging from the value of correlation coefficient (r) of 0.625 and classified in the category of being in the range of the score of 0.41 to 0.70 and if seen from the analysis regresinya stated that the quality of service positively affect the customer satisfaction BMT Darussalam Ciamis, where the quality of service influence by 22% and the rest by 78% influenced by other factors not described in this study.